Pozycja ustrojowa księcia Liechtensteinu - Bazak, Milena (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The article presents the political position of the prince in the Principality of Liechtenstein. The monarch has a wide scope of powers that allows him to have a real influence on the dominion in the state. The author aimed to show the strong position of the head of state and his connections with the legislative, executive and judiciary.
Keywords: monarchy; prince; Liechtenstein; principality